Stress reduction intervention and the initial periodontal therapy outcome in chronic periodontitis patients. a randomized controlled pilot study - Bangalore Varadhan, karthikeyan; Shanmukha Venkata Nagarjuna, Munaga; Munivenkatappa Lakshmaiah Venkatesh, Prabhuji; Jyothsna N, Sai; Bhardwaj, Smiti; Murahari, Rekha (International Journal of Dental Research, 2019)
Background: Psychosocial stress, have been implicated as risk indicators for periodontal disease. Minimal evidence in literature exists to assess the effect of stress reduction therapy (SRT) in the outcome of non-surgical periodontal therapy (NSPT).Objective: Hence, we aimed to explore the possibility of employing SRT in stressed patients as an adjunctive intervention in the management NSPT.Materials and Methods: Sixty male patients divided into Group 1 comprised of 20 unstressed chronic periodontitis patients receiving non-surgical periodontal therapy alone, Group 2a (20 stressed chronic periodontitis patients) received intervention focused on SPT with NSPT and Group 2b (20 stressed chronic periodontitis patients) received only NSPT without SPT. Their stress level was evaluated using a standard questionnaire method and salivary cortisol levels, at baseline and 3 months along with periodontal parameters.Results: There was significant reduction in stress parameters for Group 2a patients. The reduction of total periodontitis affected sites was highest in Group I patients (55.4%), followed by Group 2a patients (53.2%) and Group 2b patients (38%).Conclusion: SRT may result in comparable treatment outcome to unstressed chronic periodontitis patients. This study opens new avenues to investigate the effects of stress management as an adjunctive to conventional NSPT, which should be explored further.Â